The Influence of Electronic Visa Service Quality on Satisfaction and Intention to Return to Batam in the New Normal Era - Yuniarto Putri, Aghnia; Darma Putra, I Nyoman; Antara, Made (Riviera Publishing, 2023)
This study aims to examine the relationship between the perception of e-visa services and service quality towards the satisfaction of e-visa services with the intention of foreign tourists to revisit Batam. This research method employs a quantitative approach, targeting foreign tourists with a B211A visa index, with a sample size of 100 respondents. The sampling technique used in this research is Accidental Sampling. Data collection involved distributing questionnaires, conducting interviews with several respondents, and a literature review to complement supporting theories. The data was analyzed using Structural Equation Modeling (SEM) with SmartPLS Student Version software. The results of this study indicate that (1) perception has a significant direct influence on tourist satisfaction, does not significantly impact the intention to revisit, and is partially mediated by the intention to return to Batam; (2) the quality of e-visa services has a significant direct influence on tourist satisfaction and the intention to revisit, yet is fully mediated by the intention to return to Batam; and (3) tourist satisfaction does not significantly influence the intention to return to Batam. This research contributes academically by providing an understanding of the effectiveness of implementing e-visa services in increasing visits by foreign tourists to Batam in the new normal era. It reinforces theories related to tourist satisfaction and intentions to revisit while enriching the body of knowledge in the field of tourism and immigration studies. Additionally, this study offers practical contributions by providing scientific research data to stakeholders and policymakers in the tourism sector.